Od entuzjazmu do politycznych obaw : Europa Środkowa w poszukiwaniu nowego modelu relacji z Chinami : perspektywa polityczno-prawna - Kołtuniak, Łukasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In my article I try to analyse relations between Central Europe region and China. China is the new empire with very strong will of expansion in the new part of World. This expansion in the Central Europe began in 2012 and in the first period was perceived as the great chance by the Central European government. I want to describe the disproportion between China promise of „fast road to modernization” for the whole region and relatively small amount of real investments. We must also analyse the growing China attempt of building political influence in region. To sum up in my article I focus attention on the lack of political agenda in relation with China presenting by Central European governments and many questions connected with potentially political threats from the side of China’s government or investors
Keywords: China; economy; illiberalism; CEE; Visegrad